2018
DOI: 10.1097/phm.0000000000000783
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transcranial Direct Current Stimulation Plus Physical Therapy on Gait in Patients With Parkinson Disease

Abstract: Anodal tDCS or physical therapy could be used alone or together as a combination treatment to improve the walking speed of patients with Parkinson disease. The effects lasted for approximately 8 wks. The combination treatment was not superior to the use of tDCS or physical therapy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(79 citation statements)
references
References 28 publications
2
75
0
2
Order By: Relevance
“…Our results show a reduction of step and stance duration and an increment of lower limb velocity during TUG, S&G and NW tests. These achievements confirm the findings reported in other works, which evidenced some improvement of hypokinetic gait in PD after tDCS treatment [29,30,51].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results show a reduction of step and stance duration and an increment of lower limb velocity during TUG, S&G and NW tests. These achievements confirm the findings reported in other works, which evidenced some improvement of hypokinetic gait in PD after tDCS treatment [29,30,51].…”
Section: Discussionsupporting
confidence: 92%
“…In fact, brain activation patterns in M1 and DLPFC are extremely involved in successful locomotion performance in patients with PD [21,[25][26][27]. Further, the effectiveness of tDCS for alleviating gait and postural instability seems promising [28][29][30][31], however, evidence of its benefit remains unclear and controversial [23,32] because different tDCS protocols and target areas of scalp have been considered, leading to conflicting evidence on MDS-UPDRS scores [23,28].…”
Section: Introductionmentioning
confidence: 99%
“…To the present date, clinical studies on tDCS to treat PD symptoms have focused on two stimulation sites: primary motor cortex (M1) and dorsolateral prefrontal cortex (DLPFC). These studies have reported that anodal tDCS of M1 improves PD motor symptoms (Fregni et al, 2006 ; Benninger et al, 2010 ; Kaski et al, 2014a , b ; Valentino et al, 2014 ; Yotnuengnit et al, 2018 ), while anodal stimulation of DLPFC improves cognitive and executive functions (Boggio et al, 2006 ; Pereira et al, 2013 ; Doruk et al, 2014 ; Manenti et al, 2016 ). Since PD patients have concurrent motor and cognitive impairments, a tDCS protocol that can alleviate both types of symptoms would be an important alternative for PD therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Anodal tDCS may also induce dopamine release in the basal ganglia by the activation of glutamatergic corticostriatal fibers (Siebner et al, 1999;Fregni et al, 2006;Valentino et al, 2014). Studies have been done by targeting either the motor cortex (M1, 1-2 mA, 13-30 min) (Verheyden et al, 2013;Kaski et al, 2014b;Mak and Yu, 2014;Valentino et al, 2014;Costa-Ribeiro et al, 2016Schabrun et al, 2016;Fernandez-Lago et al, 2017;da Silva et al, 2018;Yotnuengnit et al, 2018) or the dorsolateral prefrontal cortex (DLPFC, 2 mA, 7-20 min) (Manenti et al, 2014;Lattari et al, 2017). At post-stimulation, a short-term benefit in gait was noted in most of these studies.…”
Section: Transcranial Direct Current Stimulation Idiopathic Parkinsonmentioning
confidence: 99%